Heat stress affects breathing and metabolism of chicks incubated at high temperature - Patrone, Luis Gustavo A. [UNESP]; Rocha, Aline C.G. [UNESP]; Bernardes-Ribeiro, Mariana [UNESP]; Lopes-da-Costa, Gleyce [UNESP]; Macari, Marcos [UNESP]; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP] (Elsevier, 2023)
Global warming poses serious implications to animal physiology and a gradual increase in ambient temperature affects all living organisms, particularly fast-growing selected species. We recorded ventilation (V̇E), body temperature (TB), oxygen consumption (V̇O2) and respiratory equivalent (V̇E/V̇O2) of 14-day-old (14d) male and female chicks at room air conditions, hypercapnia and hypoxia at heat stress (HS, 32 °C). These chicks had previously been exposed to control (CI, 37.5 °C) and high (HI, 39 °C) temperatures during the first 5 days of incubation. Under resting conditions, acute HS increased V̇E in HI females but not in HI males. Hypercapnia combined with heat promoted a potentiation of CO2-hyperventilatory response in HI females when compared with thermoneutral condition, whereas in HI incubated males a hypoventilation under hypercapnia and heat stress was observed compared to the CI group. Hypoxia associated with heat stress increased V̇E only in HI females. Our data indicates that females are more sensitive to thermal manipulation during incubation and it seems that the thermal embryonic manipulation, at least during the first days of development, does not improve the adaptive response of chicks to heat stress.
Keywords: Chemosensitivity; Heat stress; Incubation; Metabolism